Actively boosting network security with passive DNS. Issue 5 (May 2016) - Liu, Cricket
Abstract : The number of attacks against Domain Name System (DNS) infrastructure has grown exponentially in recent years, having increased by 200% since 2012. Exploiting this vulnerable infrastructure is a popular and often very successful tactic for causing disruption to organisations.